If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -1x = 2 Reorder the terms: -1x + -3y = 2 Solving -1x + -3y = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. -1x + -3y + 3y = 2 + 3y Combine like terms: -3y + 3y = 0 -1x + 0 = 2 + 3y -1x = 2 + 3y Divide each side by '-1'. x = -2 + -3y Simplifying x = -2 + -3y
| y-(-13)=-2 | | 2(2x-4)=4x | | x^2+3xy^3-x=3 | | y-(-1.8)=-4.8 | | 3z-7-z+3=0 | | y+2x=-6 | | 3y-2x=-2 | | 3(b+1)=4b+1 | | x-y-5=0 | | 10a^3+7a^2+1a= | | 8x+12=10x-18 | | (3m+8n)(3m-8n)= | | 12=3b+6a | | 5(10y-2)=2(2y+20) | | a+15=18 | | 50x+278=850 | | 16x-43=-33 | | 0=x^2+8x-16 | | -3=-3(1-4a) | | 7x-9=3x+31 | | 3.21-7y=10y-1.84 | | 29x^2-29x=0 | | t-1.3=-5.3 | | 7x+8=5x+10 | | (1-9a)(1-7a)= | | 3x-4+2x=21 | | (1-4a)(1-9a)= | | -3(X+4)=-8X | | 2y-2x=14 | | x^2+2x-63= | | -6(-6k+7)-8k=70 | | x*x-x=.3125 |